Assessment of a government-subsidized supermarket in a high-need area on household food availability and children's dietary intakes. Issue 15 (26th February 2015) - Elbel, Brian; Moran, Alyssa; Dixon, L Beth; Kiszko, Kamila; Cantor, Jonathan; Abrams, Courtney; Mijanovich, Tod
Abstract: Objective: To assess the impact of a new government-subsidized supermarket in a high-need area on household food availability and dietary habits in children. Design: A difference-in-difference study design was utilized. Setting: Two neighbourhoods in the Bronx, New York City. Outcomes were collected in Morrisania, the target community where the new supermarket was opened, and Highbridge, the comparison community. Subjects: Parents/caregivers of a child aged 3–10 years residing in Morrisania or Highbridge. Participants were recruited via street intercept at baseline (pre-supermarket opening) and at two follow-up periods (five weeks and one year post-supermarket opening). Results: Analysis is based on 2172 street-intercept surveys and 363 dietary recalls from a sample of predominantly low-income minorities. While there were small, inconsistent changes over the time periods, there were no appreciable differences in availability of healthful or unhealthful foods at home, or in children's dietary intake as a result of the supermarket. Conclusions: The introduction of a government-subsidized supermarket into an underserved neighbourhood in the Bronx did not result in significant changes in household food availability or children's dietary intake. Given the lack of healthful food options in underserved neighbourhoods and need for programmes that promote access, further research is needed to determine whether healthy food retail expansion, alone or with other strategies, can improve food choices of children and their families.